Knowledge, perception, and behavior of pregnant women against COVID-19 transmission - Azizah Nurdin; Syatirah Syatirah; Rini Fitriani; Mutmainnah Sari (Intelektual Pustaka Media Utama, 2022)
The outbreak of COVID-19 had a significant impact in terms of economic and social health. Assessing the community's knowledge regarding the transmission of COVID-19 is essential to specify the target of promoting and preventive actions. Therefore, the research aimed to assess pregnant women's knowledge, perception, and behavior against COVID-19 transmission. The research is a quantitative cross-sectional study. Pregnant women who received antenatal care at PKU Muhammadiyah Mamajang Makassar Hospital were included in the study. We are using random sampling, and the study was conducted from May 31, 2021 to July 31, 2021. The study found that pregnant women's knowledge, perception, and behavior of COVID-19 transmission was high and good. Several factors were found to be related to the level of knowledge, including the story of education (p 0.013), perception (p 0.037), and behavior (p 0.0001). Meanwhile, age and parity have no association with knowledge (p 0.524 and p 0.499). Currently, it is hoped that more optimal education will continue to be carried out by health workers to mothers so that they can live their pregnancies in a prosperous manner so that mothers and fetuses will be healthy and safe during the pandemic COVID-19.